Management of GIST: Perspective of Rajshahi Medical College Hospital - Uddin, Md Dayem; Hannan, ABM Abdul; Hasan, Mohibul (TAJ: Journal of Teachers Association, 2010)
A prospective study had been carried out between July 2003 and June 2010 in Radiotherapy Department of Rajshahi Medical College Hospital on the patients diagnosed as Gastrointestinal Stromal Tumor (GIST). A total of 32 patients were enrolled. Males 24(75%) Predominated over the females 8(25%) with male female ratio 3:1. The patients were between 25 and 65 years with the mean age 45 years and majority (75%) belonged to age above 40 years. Common sites of involvement were ileum 14 (40.5%), Stomach 12 (32.5%) followed by duodenum 4 (15.25%) and jejunum 2(11.75%) in descending order. All patients attended after surgery except two who was inoperable. Patients with gross residual disease were planned for oral Imatinib mesylate (400-600mg / day) as adjuvant therapy. The two inoperable cases and those with gross residual disease at primary or metastatic site were planned for palliative treatment. Imatinib mesylate 400mg/day was planned for few cases. 3 cases with gross post operative residue were treated by 50Gys radiotherapy by conventional fractions from cobalt machine. Among 20 cases who were planned for adjuvant therapy 4 completed their course of targeted therapy after four years and are on 2-3 monthly follow up are in disease free state – clinically and by investigation . Among the remaining-16 cases, two patients faced progression of the disease and died and two patients presented with liver metastasis and rest are on oral Imatinib therapy in escalating dose, now gradually improving. Among the 12 cases, who were planned for palliative therapy, 4 post operative cases with gross residual mass, died due to disease progression. 2 post operative cases with gross residual disease, who received radiotherapy, did not come for subsequent follow up. Other 6 cases are yet on Imatinib and the tumor masses are regressing gradually. TAJ 2010; 23(1): 1-5